2020
DOI: 10.1136/bjophthalmol-2020-316169
|View full text |Cite
|
Sign up to set email alerts
|

Progressive retinal nerve fibre layer thinning and choroidal microvasculature dropout at the location of disc haemorrhage in glaucoma

Abstract: Background/AimsTo investigate whether parapapillary choroidal microvasculature dropout (MvD) is associated with progressive retinal nerve fibre layer (RNFL) thinning in eyes with primary open-angle glaucoma (POAG) and disc haemorrhage (DH).MethodsParapapillary microvasculature was evaluated by swept-source optical coherence tomography (OCT) angiography (OCTA) in 50 eyes with POAG and DH, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Figure 2 C and Table 2 show the strong correlation between the angular width and location of the MvD, RNFL defect, and βPPA–RNFL defect superimposition in the entire study group (all P < 0.001), in concert with previous reports. 9 , 13 , 14 Notably, the strength of the correlation was consistently higher in the βPPA–RNFL defect superimposition than in the RNFL defect alone; in NAION, the correlation between the angular width of MvD and RNFL defects was insignificant ( P = 0.090), while the βPPA–RNFL defect superimposition successfully demonstrated a significant relationship ( P = 0.016).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Figure 2 C and Table 2 show the strong correlation between the angular width and location of the MvD, RNFL defect, and βPPA–RNFL defect superimposition in the entire study group (all P < 0.001), in concert with previous reports. 9 , 13 , 14 Notably, the strength of the correlation was consistently higher in the βPPA–RNFL defect superimposition than in the RNFL defect alone; in NAION, the correlation between the angular width of MvD and RNFL defects was insignificant ( P = 0.090), while the βPPA–RNFL defect superimposition successfully demonstrated a significant relationship ( P = 0.016).…”
Section: Resultsmentioning
confidence: 96%
“…Most of all, the spatial correspondence between RNFL defect and MvD in many studies was interpreted to indicate that MvD may be a finding associated with, and as a result of, the RNFL defect. 9 , 13 , 14 The proportional enlargement of MvD with glaucoma progression also indicates that MvD may not precede the chronic progressive damage in glaucoma. 4 , 5 , 19 Son et al 13 reported that MvD is observed only at the location of the RNFL defect in eyes with hemiretina involvement and is usually found in the location of more severe RNFL defects in eyes with bi-hemiretinal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in agreement with previous studies using pulse amplitude and other relevant parameters of ocular blood ow to evaluate choroidal perfusion 23,24 . Decreased retinal nerve ber layer and choroidal thickness accompanied by subsequent disc hemorrhage has been linked to myopia 25 . A decline in choriocapillary perfusion may arise from reduced blood demands secondary to choroidal degeneration occurring in highly myopic eyes.…”
Section: Discussionmentioning
confidence: 99%